2020
DOI: 10.1038/s41598-020-58267-1
|View full text |Cite
|
Sign up to set email alerts
|

p53 dynamics in single cells are temperature-sensitive

Abstract: Cells need to preserve genome integrity despite varying cellular and physical states. p53, the guardian of the genome, plays a crucial role in the cellular response to DNA damage by triggering cell cycle arrest, apoptosis or senescence. Mutations in p53 or alterations in its regulatory network are major driving forces in tumorigenesis. As multiple studies indicate beneficial effects for hyperthermic treatments during radiation-or chemotherapy of human cancers, we aimed to understand how p53 dynamics after geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…This could affect the capability of p53 to bind different ligands and, more generally, the p53 functionality. In this respect, it has been recently observed that a change in p53 dynamics with temperature from 33 to 39 °C is related to the increased capability of the cell to preserve the genetic integrity …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could affect the capability of p53 to bind different ligands and, more generally, the p53 functionality. In this respect, it has been recently observed that a change in p53 dynamics with temperature from 33 to 39 °C is related to the increased capability of the cell to preserve the genetic integrity …”
Section: Results and Discussionmentioning
confidence: 99%
“…In this respect, it has been recently observed that a change in p53 dynamics with temperature from 33 to 39 °C is related to the increased capability of the cell to preserve the genetic integrity. 51 MD Simulation Results. To get further information about the effects of temperature on the structure and dynamics of DBD, with particular attention to the Trp146 environment, we have performed MD simulations of DBD in water.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“… 25 , 33 Cellular heat shock increases expression of p53 and leads to its phosphorylation and subsequent tetramer formation in the nucleus. This results in stabilisation of p53 39 , 40 , 41 , 42 which can then activate transcription of HSP70, leading to the heat shock response and apoptosis. 43 Our data suggest a heat-shock-induced reduction in E6 protein levels, which should add to the increased p53 levels due to hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…This switch would reduce oxygen consumption rate, thereby contributing to reoxygenation. (2) Mild temperature heating has been reported to induce apoptosis and/or senescence in some tumor cell types in vitro and in vivo [ 145 , 146 ]. The induction of apoptosis and senescence would reduce oxygen consumption rate.…”
Section: Returning Back To Differences In Temperature Distributions B...mentioning
confidence: 99%